ECO-CONNECTIVITY OF ARTS LEARNING FOR MENTALLY DISABLED CHILDREN AT SLB GEDANGAN SIDOARJO EAST JAVA - Ika Anggun Camelia (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This study aimed to explore the concept of eco-connectivity appeared in online-based distance learning (PJJ) for mentally disabled children. Furthermore, this study aimed to provide an understand about the need for developing learning models towards the current conventional learning models. Qualitative research with a case study approach was utilized in this study to examine the phenomenon of eco-connectivity of art learning for mentally disabled children at SLB Gedangan Sidoarjo, East Java. The research subjects were IB and AM, the mentally disabled children C at SLB Gedangan Sidoarjo, East Java. This research was conducted from September 2020 to January 2021. The data obtained were analyzed based on John Dewey’ point of view about art education and its existence, Cathy Malchiodi about education for children with special needs, and the learning connectivity by George Siemens. The results showed that eco-connectivity maximized teachers' role in adjusting circumstances by designing learning according to essential competencies and making tutorials assisting children's learning with the help of children's learning environments. Eco-connectivity was also seen in the assessment process by reviewing children's work and interviews with parents. This provided a comprehensive assessment, which further strengthened teachers, parents, and the environment to support mentally disabled children's competence through art learning.